Field Evaluation of a Single Row Manual Vegetable Transplanter in Comparison with Traditional Method - Kumar, Vinay (Indian Journal of Hill Farming, 2018)
Present study was carried out during the year 2015-16 to evaluate the single row manual vegetable transplanter on three vegetable crops i.e. brinjal, chilli and tomato at two differentsites and compare it with traditional method of transplanting. The manual single row vegetable transplanter consists of different component like hopper, handle, seedling delivery tube, jaw opening lever and jaw mouth. The results obtained from the trial tests concluded that transplanter functioned properly as there is no miss planting, also the rate of tilted planting is negligible. From visual observations it was observed that there was no damage tothe seedling during operation. The transplanting mean effective field capacity observed from trial was 0.029 ha/h, mean field efficiency was 91.34% and mean labour requirement was 35.87 man-hr/hr with single row manual vegetable transplanter. The transplanting mean effective field capacity observed from trial with traditional method was 0.014 ha/h, mean field efficiency was 90.64% and mean labour requirement was 75.85 man-hr/hr. The mean effective field capacity was 52.36 per cent higher over traditional method of transplanting. Significantly lower labour was required with developed prototype over traditional methodwith an average saving of 52.83 per cent of time and labour.